Expressive Copying Behavior for Social Agents: A Perceptual Analysis - Castellano, G.; Mancini, M.; Peters, C.; McOwan, P. W. (IEEE transactions on systems, man and cybernetics. Part A, Systems and humans, 2012)
Successful human interaction commonly involves prototypical exchanges where interactors are engaged, synchronized, and harmonious in their behaviors. The copying of aspects of the other's behavior, at different levels, seems central to establishing and maintaining such empathic connections. Yet, many questions remain unanswered, particularly how it is possible to reflect the same affective content back to the other when the actual motion itself is not exactly the same as theirs. This paper presents a perceptual study in which emotional gestures conducted by an actor were mapped onto synthesized versions generated by an embodied virtual agent. Copying is at the expressive level, where qualities such as the fluidity or expansiveness of gestures are considered, rather than exact low-level motion matching. Participants were later asked to rate the emotional content of video recordings of both the original and the synthesized gestures. A statistical analysis shows that, in most cases, participants associated the emotional content of the agent's gestures with that intended to be expressed by the original actor. The results suggest that a combination of the type of movement performed and its quality is important for successfully communicating emotions.